Numerical analysis of processes for the formation of moonlets confining the arcs of Neptune - Madeira, Gustavo [UNESP]; Winter, Silvia M. Giuliatti [UNESP] (Oxford University Press (OUP), 2022)
The arcs of Neptune-Fraternite, Egalite, Liberte, and Courage- A re four incomplete rings immersed in the Adams ring. A recent confinement model for the arcs proposes that the structures are azimuthally confined by four co-orbital moonlets. In this work, we intend to approach some points related to the dynamics of co-orbital moonlets and suggest a model for their formation. We study the equilibrium configurations for 1+N co-orbital satellites under the 42:43 Lindblad resonance with Galatea. We obtained three distinct configurations with 1+3 and 1+4 moonlets able to confine and reproduce the location of the arcs. The moonlets' formation is analysed by the disruption of an ancient body at a Lagrangian point of a moon. The disruption fragments spread out in horseshoe orbits and collide to form moonlets, which reach an equilibrium configuration due to a non-conservative effect. In such a scenario, the arcs likely formed through a mixture of different processes, with impacts between disruption outcomes and meteoroid impacts with the moonlets being possibilities.
Keywords: celestial mechanics; planets and satellites: Dynamical evolution and stability; planets and satellites: Formation; planets and satellites: Rings